The Praise of Self-Instruction in the 21st Century - against a Background of Selected Concepts of Self-Education in Poland during the Partitions and Interwar Period - Katarzyna Wrońska (Nicolaus Copernicus University in Toruń, 2020)
In the text, the author considers the present sense and meaning of self-instruction - in connection to the issue of being alone - against a background of selected historical concepts of self-education in Poland. Considering education and its role in learning to think, the author assumes that being alone as a mode of human existence is a philosophical starting point. Therefore, self-instruction presents itself as an adequate example, illustrating the possibility of experiencing solitude and learning to be alone as a way of being a person. In the times of the partitions, self-instruction was a very popular postulate among Polish intellectuals involved in activities promoting civil and patriotic attitudes, in a country subjected to denationalising politics. In the interwar period, the concepts of self-instruction were still developing, due to defects in the created official school system at the time. The author focuses on one such concept, created by Władysław M. Kozłowski. Kozłowski himself assessed his work for the education of compatriots as fulfilling a civil duty and acting for a free and democratic Poland. Today, recalling the concept of self-instruction allows us to see it as a necessary humanizing complement to school education in Poland, balancing between the extremes of encyclopaedism and instrumentalism. It can be used to bring out a few arguments for education not being reduced to professionalisation and which promotes the human condition as vita activa.